Language Data in National Population and Housing Census of Nepal 2021: A Critical Analysis - Chalise, Krishna Prasad (Nepalese Linguistics, 2024)
Analysis of NPHC 2021 language data based on retention of ancestral language as MT and MT in ethnic population, increase in MT and SL speakers after the previous census. Among them 39, 25, and 53 languages have problems with the first, second, and third variables respectively; and all have problems with the fourth variable. Unclear questions, improper technical word definitions, organized activities of caste/ethnic organizations and activists to influence the answers, and insufficient training for the enumerators are responsible for the problems. The post-enumeration survey did not include language data for validity and reliability evaluation. Future language policies and planning based solely on census data will lead to serious problems.